The 7 habits of highly effective teens (7 kebiasaan remaja yang sangat efektif) Sean Covey ; alih bahasa, Arvin Saputra ; editor, Lyndan Saputra - COVEY, Sean; Saputra, Lydan; Saputra, Arvin (2001)
306 hlm ilus 24 cm